FSHD1 Diagnosis in a Russian Population Using a qPCR-Based Approach - Nikolay Vladimirovich Zernov; Anna Alekseevna Guskova; Mikhail Yurevich Skoblov (Diagnostics, 2021)
Facioscapulohumeral dystrophy (FSHD) is an autosomal dominant myodystrophy. Approximately 95% of cases of FSHD are caused by partial deletion of the D4Z4 macrosatellite tandem repeats on chromosome 4q35. The existing FSHD1 diagnostic methods are laborious and not widely used. Here, we present a comprehensive analysis of the currently used diagnostic methods (Southern blotting and molecular combing) against a new qPCR-based approach for FSHD1 diagnosis. We observed 93% concordance between the results obtained by the new qPCR-based approach, reference Southern blotting and molecular combing methods. Applying the qPCR-based approach in the studied population, we observed a prevalence (64.9%) of the permissive alleles in the range of 3–6 D4Z4 units for a group of patients, while in a group of carriers, the permissive alleles were mostly (84.6%) present in the range of 6–9 D4Z4 units. No prevalence of disease penetrance depending on gender was observed. The results confirmed the earlier established inverse correlation between permissive allele size and disease severity, disease penetrance. The results suggest the applicability of the qPCR-based approach for FSHD1 diagnosis and its robustness in a basic molecular genetics laboratory. To our knowledge, this is the first study of FSHD1 permissive allele distribution in a Russian population.